(untitled) (REMUNOM, 2026)
The inajá is a typical Amazonian fruit from a palm tree, highly appreciated in the region, consumed fresh or in derived forms, such as sweets. This work sought to characterize inajá fruits from Abaetetuba, Pará, in physical/biometric terms and their pulps in physicochemical terms. The results showed that the fruits have an ellipsoidal to ovoid shape, with good pulp yield. The pulp was shown to be slightly acidic, with an average moisture content and other variables compatible with existing literature. The analyzed inajá fruits and pulps can be considered of good quality and suitable for agro-industrial use.